If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = v + -8 Reorder the terms: 1 = -8 + v Solving 1 = -8 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 1 + -1v = -8 + v + -1v Combine like terms: v + -1v = 0 1 + -1v = -8 + 0 1 + -1v = -8 Add '-1' to each side of the equation. 1 + -1 + -1v = -8 + -1 Combine like terms: 1 + -1 = 0 0 + -1v = -8 + -1 -1v = -8 + -1 Combine like terms: -8 + -1 = -9 -1v = -9 Divide each side by '-1'. v = 9 Simplifying v = 9
| -5-4r=-(1-2r) | | -9=2+p | | 8x-(5-x)+2(3x-4)=2 | | 3x^2=-18 | | 3r-4=5(r-1) | | 3k=45 | | 2(7/2)+y=11 | | 3(x-2)=-31+4x | | 8m+m-m-3m+2m=14 | | 3(2x+5)-5= | | 19s-13s-6s+s=19 | | 8.8=m-14.4 | | 7x+2y=94 | | 152+8x=-82-10x | | v^2-5vy-14y^2=0 | | 5r-1=-3(-4+3r)+r | | 2y=7x-94 | | (2s-9)(8s+1)=0 | | 19s-13s-6s=19 | | 3c+2=6c | | 5(m+9)=40+2m+5+3m | | 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 | | -(6x-2y-2)= | | 42s+s^2-s^3=0 | | 6x+9=9x-6 | | 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 |